Interpatient heterogeneity in hepatic microvascular blood flow during vascular inflow occlusion (Pringle manoeuvre) - Shen, Lucinda (Hepatobiliary Surg Nutr, 2020)
BACKGROUND: Vascular inflow occlusion (VIO) during liver resections (Pringle manoeuvre) can be applied to reduce blood loss, however may at the same time, give rise to ischemia-reperfusion injury (IRI). The aim of this study was to assess the characteristics of hepatic microvascular perfusion during VIO in patients undergoing major liver resection. METHODS: Assessment of hepatic microcirculation was performed using a handheld vital microscope (HVM) at the beginning of surgery, end of VIO (20 minutes) and during reperfusion after the termination of VIO. The microcirculatory parameters assessed were: functional capillary density (FCD), microvascular flow index (MFI) and sinusoidal diameter (SinD). RESULTS: A total of 15 patients underwent VIO; 8 patients showed hepatic microvascular perfusion despite VIO (partial responders) and 7 patients showed complete cessation of hepatic microvascular perfusion (full responders). Functional microvascular parameters and blood flow levels were significantly higher in the partial responders when compared to the full responders during VIO (FCD: 0.84±0.88 vs. 0.00±0.00 mm/mm(2), P<0.03, respectively, and MFI: 0.69–0.22 vs. 0.00±0.00, P<0.01, respectively). CONCLUSIONS: An interpatient heterogeneous response in hepatic microvascular blood flow was observed upon VIO. This may explain why clinical strategies to protect the liver against IRI lacked consistency.